2015
DOI: 10.1007/s40496-015-0045-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of Optical Coherence Tomography (OCT) for Diagnosis of Caries, Cracks, and Defects of Restorations

Abstract: Optical coherence tomography (OCT) is a noninvasive technique providing cross-sectional images of a tooth structure. This review describes the use of OCT for detecting dental caries, tooth fractures, and interfacial gaps in intraoral restorations. OCT can be a reliable and an accurate method and a safer alternative to X-ray radiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
99
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 81 publications
(170 reference statements)
0
99
0
2
Order By: Relevance
“…In vitro studies showed an adequate to strong agreement, when SS-or SD-OCT were compared to histology [29,42,43], confocal microscopy, X-ray microtomography, or transverse microradiography and a diagnostic superiority compared to bitewing radiography [44] (Figures 1, 2, 5-11 and 14). In vitro studies showed an adequate to strong agreement, when SS-or SD-OCT were compared to histology [29,42,43], confocal microscopy, X-ray microtomography, or transverse microradiography and a diagnostic superiority compared to bitewing radiography [44] (Figures 1, 2 and 5-11 and 14). Image contrast and the spatial separation of the lesion body versus sound enamel can be further enhanced using polarization-sensitive OCT [45].…”
Section: Caries Diagnosismentioning
confidence: 96%
See 2 more Smart Citations
“…In vitro studies showed an adequate to strong agreement, when SS-or SD-OCT were compared to histology [29,42,43], confocal microscopy, X-ray microtomography, or transverse microradiography and a diagnostic superiority compared to bitewing radiography [44] (Figures 1, 2, 5-11 and 14). In vitro studies showed an adequate to strong agreement, when SS-or SD-OCT were compared to histology [29,42,43], confocal microscopy, X-ray microtomography, or transverse microradiography and a diagnostic superiority compared to bitewing radiography [44] (Figures 1, 2 and 5-11 and 14). Image contrast and the spatial separation of the lesion body versus sound enamel can be further enhanced using polarization-sensitive OCT [45].…”
Section: Caries Diagnosismentioning
confidence: 96%
“…At this stage, the subsurface enamel porosity can be stopped or reversed using appropriate non-or minimally invasive therapies and biofilm control [8]. White spot lesions appear whitish as the incident light is backscattered off porous regions to a considerable extent [29,39]. OCT makes use of the same phenomenon.…”
Section: Caries Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…It constructs images from the back-scattered light of a transilluminated tissue, based on the differences in the optical absorption and scattering properties of the tissue (51,52). OCT has been used in several clinical applications including dermatology (53,54), gastroenterology (55), ophthalmology (56), and dentistry (57,58).…”
Section: Optical Coherence Tomography (Oct)mentioning
confidence: 99%
“…Other methods include optical instruments, fiber-optic sensing method, mercury dilatometer, electromagnetic balance and video imaging 12) . Contemporary 2D and 3D imaging methods have been used to analyze in a non-invasive and non-destructive way the behavior of materials inside a standardized cavity, such as finite element analysis 18,21,22) , optical coherence tomography 7,23) , and micro-computed tomography (µCT) 19,22) . These methods have been widely described in literature, due to reliable and significant results 7,18,24,25) .…”
Section: Introductionmentioning
confidence: 99%